Pengembangan Objek Wisata Pasar Kamu Sebagai Wisata Kuliner Unggulan Di Desa Denai Lama Deli Serdang - Zaudrey, Muhammad; Winata, Edi (Jurnal Akademi Pariwisata Medan, 2023)
Abstract This research is entitled "Development of Pasar Kamu Tourism Object as a Leading Culinary Tourism in Denai Lama Deli Serdang Village". The purpose of this research is an effort to introduce your Market attractions to readers. This research was located in Denai Lama Village, Pantai Labu District, Deli Serdang Regency, North Sumatra. The method used in this study is a qualitative research method where this research focuses on the introduction and development of Pasar Kamu culinary tourism.  The data collection methods carried out in this study are observation, interviews and documentation. The types of data used to conduct this study are primary data and secondary data. This study will take place from March 2023 to May 2023. The result of this study is that the author knows that Pasar Kamu stands for Pekan Sarapan Karya Anak Muda, where Pasar Kamu was formed based on the manager's desire to create a Pekan sheltered by young people from Denai Lama Village. The manager wants to re-introduce traditional culinary to the community, especially the younger generation through this week. To create a creative and innovative Breakfast Week, the manager makes a uniqueness in the transaction tool in your market, namely by using tempu as legal tender. Tempu is made of coconut shells which is shaped like a coin, where coconut shells are natural resources that are found in Denai Lama Village. With this uniqueness, the manager managed to bring many tourists from outside Pantai Labu District to visit to enjoy traditional culinary served in the midst of a lush atmosphere of bamboo trees and coconut trees. That way the manager has succeeded in developing your Market as a culinary tourism destination that must be visited in Deli Serdang. Keywords : Deli Serdang, Traditional Culinary, Tourist Attractions, Pasar Kamu